Experimental investigations into stress sensitivity in three Chinese coal samples by NMR. Issue 1 (31st March 2022) - Zhu, Qingzhong; Xiao, Qianhua; Meng, Yanjun; Zuo, Yinqing; Cheng, Xiangzhen; Zhang, Yixuan
ABSTRACT: The coal reservoirs have low mechanical strength and strong stress sensitivity. The study of stress sensitivity is of great significance to the efficient development of coalbed methane (CBM). In order to reveal the stress and strain characteristics of coal reservoirs, the low-field nuclear magnetic resonance (NMR) experiments with variable confining pressures were carried out on three coal samples from China. Based on the T2 spectrum of coal samples under different confining pressures, the pore distribution, connectivity, and porosity variation rules of the coal samples were analyzed. Results show that the peaks of mesopore, macropore-fissure in the coal samples are well developed; however, the micropore peaks are poorly developed. There are differences in the stress deformation of pores and fractures in coals. With increasing confining pressures from 0 to 16 MPa, the peak of fractures decrease most obvious, and the peak of mesopore and macropore-fissure are relatively obvious, while the peak of the small pores is not significantly reduced. With the confining pressure increases, the total NMR porosity of coal decreases as the rule of negative exponential function, which is mainly controlled by changes of the porosity of seepage pore. The effect of adsorption pore on porosity changes is not obvious.